Implementação da educação em tempo integral nas escolas socioeducativas paraibanas: desafios e perspectivas - Brito, Vanessa Araújo Toscano de (2020)
It started, five years ago, in Paraíba a process of implementing full-time schools in its state education network. In 2017, a reformulation of Paraíba social and educational system was carried out and the same educational proposal was implemented in the schools of this system. In view of the changes that have occurred, we work with the analysis of the implementation process of the proposal for full-time education in the context of deprivation of liberty, as well as the adaptations that are necessary, considering the specificities of the environment. The turnover in deprivation of liberty spaces is high, so there are young people who will stay between three months and up to three years in these spaces. Therefore, there is an urgent need to understand how the new pedagogical and educational management structure is working in socio-educational school institutions and to understand whether it is in fact providing an opening for adolescents to project a different future. With regard to the theoretical relevance of the theme, there is a scarcity of studies in the area, since Paraíba is the first state in the country to adopt an educational policy throughout its socio-educational system that creates parameters for full-time education. In view of the above, this work had the general objective of analyzing how full-time educational policy is being implemented in socio-educational schools in Paraíba, and as specific objectives: to investigate what the literature on adolescence and juvenile delinquency says, in face of national and international legal provisions about childhood and adolescence; comprehend the structure and functioning of Paraiba's Socio-Educational Units, characterizing the structure of the full-time school in the State of Paraíba; and to point out considerations about the implementation process based on the managers' speech. This is an exploratory field study with a qualitative approach, in the form of a case study, whose instrument used to collect the data was a semi-structured interview containing six questions, conducted with ten members who were or currently are part of the team that was responsible for implementing the full-time education policy at the “Alice de Almeida” Child and Adolescent Development Foundation (FUNDAC) and the State Department for Education, Science and Technology (SEECT) in Paraíba. The data obtained during the collection were analyzed in the light of Bardin's reference about Content Analysis. As a result, we realize that the school has brought several benefits to education, in its entirety, in the lives of adolescents deprived of their liberty, however there are still challenges to be overcome for the school to function in a way that promotes a different praxis in their lives.